2021
DOI: 10.3390/genes12071003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Drug-Resistance Acinetobacter baumannii under the Stress Condition Caused by Litsea cubeba L. Essential Oil via RNA Sequencing

Abstract: Litsea cubeba L. essential oil (LCEO) can affect the growth of drug-resistance bacteria. However, research on stress response of drug-resistant A. baumannii under sub-lethal LCEO concentrations had been limited so far. Therefore, transcriptomic analysis of A. baumannii under 1/2 minimum inhibitory concentration (MIC, 0.54 mg/mL) of LCEO was performed. Results of transcriptomic analysis showed that 320/352 genes were significantly up/down-regulated, respectively, in LCEO-treated A. baumannii. Both up and down-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
5
1
Order By: Relevance
“…The MBIC value for amoxicillin was 625 µg/mL in this study, in contrast to other studies, which revealed the MBIC value as being 800 µg/mL [ 11 ]. In comparison to the result for amoxicillin, the different silica NPs (pure, composite, alkali, and H 3 PO 4 .SiO 2 ) used in this study showed an inhibition effect for the biofilm by reducing absorbance values at various concentrations (from 1.0 mg/mL to 0.125 mg/mL), according to Figure 6 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The MBIC value for amoxicillin was 625 µg/mL in this study, in contrast to other studies, which revealed the MBIC value as being 800 µg/mL [ 11 ]. In comparison to the result for amoxicillin, the different silica NPs (pure, composite, alkali, and H 3 PO 4 .SiO 2 ) used in this study showed an inhibition effect for the biofilm by reducing absorbance values at various concentrations (from 1.0 mg/mL to 0.125 mg/mL), according to Figure 6 .…”
Section: Discussioncontrasting
confidence: 99%
“…It has the potential to produce biofilm and cause infections in both individuals who have been hospitalized for extended durations as well as those who have been exposed to prolonged antimicrobial therapy [ 8 , 9 , 10 ]. It has been observed that A. baumannii , which is resistant to antibiotics, exhibits a robust ability to form biofilms [ 11 ]. The ability of bacterial cells to coordinate their gene expression through quorum sensing (QS) allows for the development of a multi-drug resistance feature that enables adaptation to change in environmental conditions, specifically in the form of biofilm [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, H0N28_14510 encoding the two-component system sensor histidine kinase PmrB, H0N28_14515 encoding the DNA-binding response regulator PmrA, H0N28_00400 encoding imidazolone propionase, and hutG encoding formimidoylglutamase were significantly downregulated ( Table 3 ). The changes in the expression of these genes were similar to those in A. baumannii treated with L. cubeba essential oil [ 28 ]. Based on the findings of cell content leakage, SEM, and additional integration with the transcriptome data, X33AMOP interferes with the cell membrane to exert an effect on it.…”
Section: Discussionmentioning
confidence: 86%
“…The killing effect of LC-EO on other bacteria also shows this trend. Time dependence and concentration dependence were characteristic of the reduction in drug-resistant Acinetobacter baumannii , as determined by measuring OD 600 nm at intervals [ 49 ]. Thielmann et al [ 50 ] reported that on the surface of food packaging films and across the gas phase, LC-EO achieved bactericidal effects against E. coli in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%